2008
DOI: 10.1029/2007ja012575
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet analysis of high‐latitude electric and magnetic fluctuations observed by the Dynamic Explorer 2 satellite

Abstract: [1] Wavelet analysis has been performed on the low-frequency (0.1 to 16 Hz) electric and magnetic field variations observed by the low-altitude polar-orbiting Dynamic Explorer 2 (DE2) spacecraft. The application of the wavelet transform is conditioned by the fact that both magnetic and electric signals, as well as their ratio, vary along the spacecraft track. They grow from low values in the middle latitudes to the peak values in the center of the auroral zone and then subside in the transition to the polar ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…This makes the thermosphere‐ionosphere an interesting region to study various scales of variability. There is an increasing number of studies investigating turbulence in the auroral ionosphere [e.g., Kozelov et al , 2008; Lund , 2010].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes the thermosphere‐ionosphere an interesting region to study various scales of variability. There is an increasing number of studies investigating turbulence in the auroral ionosphere [e.g., Kozelov et al , 2008; Lund , 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical models are typically used to represent the overall structure and variations of the atmosphere. However, observations indicate that there is a remarkable variability, for example, in ionospheric ion flows [ Johnson and Heelis , 2005; Bristow , 2008], electric fields [ Heppner et al , 1993; Matsuo et al , 2003; Kozelov et al , 2008], composition [ Kil et al , 2011], Joule heating [ Rodger et al , 2001], and vertical winds [ Innis and Conde , 2001; Anderson et al , 2011] in the upper atmosphere that is missing in empirical models. The term variability is often used to describe the variations of the system that are not represented by empirical models.…”
Section: Introductionmentioning
confidence: 99%
“…The electric field fluctuations in both the auroral zone and the polar cap were found to exhibit similar scaling characteristics suggesting the same nature of the drivers of turbulence in the two regions. All these results are consistent with other works which have suggested that small‐scale variations of the ionospheric electric field are generally in an intermittent turbulent state (e.g., Golovchanskaya et al, ; Heppner et al, ; Kintner Jr., ; Kozelov et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure compares the spectra of FAC and the magnetic perturbation (d B y ) in the east‐west direction along one specific pole pass track. The d B y is known to have a similar spectrum as the electric field in the north‐south direction ( E x ; e.g., Kozelov et al, ; Sugiura, ; Sugiura et al, ; Weimer et al, ). As revealed by Figure , the spectrum of the FAC is roughly constant with scale size while the spectrum of the electric field magnitude decreases with decreasing scale size.…”
Section: Resultsmentioning
confidence: 99%